Capsular Contracture In Silicone Breast Implants: Insights From Rat Models - VIEIRA,VILBERTO J. (2016)
ABSTRACT Breast augmentation with silicone implants is one of the most common procedures performed by plastic surgeons around the world. Capsular contracture is a frequent complication in breast augmentation and reconstructive surgery, that requires invasive intervention. The inflammatory response to implanted mammary prostheses appears to be directly associated to capsular contracture. This review discusses the evidences from rat models studies, on the role of inflammation and fibrosis in capsular contraction and its relation to silicone breast implants surface.